The effect of same-sex marriage legalization on interstate migration in the United States - Miriam Marcén; Marina Morales (Global Labor Organization (GLO), 2019)
The aim of this paper is to analyze the impact of marriage regulation on the migratory behavior of individuals using the history of the liberalization of same-sex marriage across the United States. Because the approval of same-sex marriage allows homosexuals access to legal rights and social benefits, marriage becomes more attractive relative to singlehood or other forms of partnership. The differences in the value of other forms of relationship status relative to marriage can affect the migration decisions of individuals, to the extent that those states approving same-sex marriage can be considered less discriminatory. Results show that that legal reform permanently increased the migration flow of homosexuals moving to tolerant states (i.e., those that have legalized same-sex marriage). The physical distance among states does not appear to be driving our estimates since the migration flow of homosexuals is not limited to border or close states. Supplemental analysis, developed to explore whether the migration flow is translated to a significant effect to the stock of homosexuals by state, suggests that that stock increased after the approval of same-sex marriage but that it was transitory, pointing to a `no effect' on the spatial distribution of homosexuals as times went by. The liberalization of marriage for homosexuals also has an effect on the migration behavior of those individuals originating from countries in which same-sex sexual activity is illegal, for whom we observe an outflow migration from those states with same sex marriage, pointing to dissimilarities in cultural aspects related to homosexuality as important factors in migration decisions.
Keywords: J12; J15; Z13; 330; Homosexuals; marriage; migration